Venomics of New World pit vipers: Genus-wide comparisons of venom proteomes across Agkistrodon - Lomonte, Bruno (J Proteomics, 2013)
We report a genus-wide comparison of venom proteome variation across New World pit vipers in the genus Agkistrodon. Despite the wide variety of habitats occupied by this genus and that all its taxa feed on diverse species of vertebrates and invertebrate prey, the venom proteomes of copperheads, cottonmouths, and cantils are remarkably similar, both in the type and relative abundance of their different toxin families. The venoms from all the eleven species and subspecies sampled showed relatively similar proteolytic and PLA(2) activities. In contrast, quantitative differences were observed in hemorrhagic and myotoxic activities in mice. The highest myotoxic activity was observed with the venoms of A. b. bilineatus, followed by A. p. piscivorus, whereas the venoms of A. c. contortrix and A. p. leucostoma induced the lowest myotoxic activity. The venoms of Agkistrodon bilineatus subspecies showed the highest hemorrhagic activity and A. c. contortrix the lowest. Compositional and toxicological analyses agree with clinical observations of envenomations by Agkistrodon in the USA and Central America. A comparative analysis of Agkistrodon shows that venom divergence tracks phylogeny of this genus to a greater extent than in Sistrurus rattlesnakes, suggesting that the distinct natural histories of Agkistrodon and Sistrurus clades may have played a key role in molding the patterns of evolution of their venom protein genes. BIOLOGICAL SIGNIFICANCE: A deep understanding of the structural and functional profiles of venoms and of the principles governing the evolution of venomous systems is a goal of venomics. Isolated proteomics analyses have been conducted on venoms from many species of vipers and pit vipers. However, making sense of these large inventories of data requires the integration of this information across multiple species to identify evolutionary and ecological trends. Our genus-wide venomics study provides a comprehensive overview of the toxic arsenal across Agkistrodon and a ground for understanding the natural histories of, and clinical observations of envenomations by, species of this genus.